(untitled) (Research, Society and Development, 2022)
Due to the high rates of oral infections, in parallel with the need for new antimicrobial methods, herbal medicines have been the choice with effective action and less toxicity, when vigorously standardized. The medicinal plant Commiphora leptophloeos (Mart.) JB Gillett, popularly known as imburana-de-espinho, found in the Caatinga biome, has been researched for this purpose. Thus, the objective of the research is to investigate in vitro the antimicrobial, bactericidal and anti-adherent action of the hydroethanolic extract of the stem bark of Commiphora leptophloeos (Mart.) J.B. Gillett on Streptococcus mutans. After making the extract, 3 experiments were carried out: determination of the minimum inhibitory concentration (MIC) of the extract from the stem bark of C. leptophloeos; determination of adhesion minimum inhibitory concentration (MICA) and; determination of bactericidal kinetics (BC) with S. mutans culture. The result for the MIC was the 1:16 dilution (3,125 x 10-2 g/mL), while the CIMA was the 1:128 dilution (3,90625 x 10-3 g/mL) and CB showed bacterial growth 2 hours after the contact of the extract with the bacteria. The conclusion of the present study is that the extract has bacteriostatic and anti-adherent action, however, the bactericidal kinetics needs further studies.